Kecurangan Pelaporan Keuangan pada Pemerintah Daerah di Indonesia: Pengujian Peran Aspek Religiusitas - Cipta, Wayan (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to examine the role of publicity and religiosity as a mitigating factor for fraudulent financial reporting in government organizations where there is pressure to obey superiors to commit unethical behavior. The data were collected by conducting an experimental study with a 2x2x1 between-subjects design on 222 final-year accounting undergraduate students. Conducting the Chi-Square analysis, the results indicated that (a) obedience pressure have a positive impact on fraudulent financial reporting; (b) publicity of financial report compiler as well as the level of religiosity have a negative impact on fraudulent financial reporting; and (c) both publicity of financial report compiler and the level of religiosity have a negative interaction with obedience pressure in influencing fraudulent financial reporting.